Stagnation point flow of radiative Oldroyd-B nanofluid over a rotating disk. (July 2020) - Hafeez, Abdul; Khan, Masood; Ahmed, Jawad
Highlights: Three-dimensional Oldroyd-B fluid flow carrying magnetized nanoparticles is investigated. The flow is generated by a rotating disk. The magnetic field is applied along z-direction. The nonlinear thermal radiation is taken to enhance the heat transfer performance. The BVP Midrich technique is utilized in Maple to acquire numerical solution. Abstract: Background: Nanofluids are known for better heat transfer characteristics in many heat exchanger devices due to their enhanced heat transfer abilities. Recently, scientists give the idea of nanofluid which is the mixture of base fluid and solid nanoparticles having very small size. For physical phenomenon of conventional fluids by mean of suspensions of nanoparticles in base fluids and prompted produce a new composite known as "nanofluids". These composite contain the nanoparticles with 1–100 nm sized which are suspended in the base fluids. Here we have considered a subclass of non-Newtonian fluid called Oldroyd-B fluid. The fluid motion over the disk surface is produced due to the rotation as well as radially stretching of disk. Further, the impact of non-linear thermal radiation and heat generation/absorption is introduced to visualize the heat transfer behavior. The convective boundary is also taken into consideration in order to investigate the fluid thermal characteristics. The novel features of thermophoresis and Brownian motion during the nanoparticles movement in fluid motion are studied with revised Buongiorno model. The physical problem is modeled with the concept of classical Fourier's and Fick's laws. The von Karman variables are used to convert the partial differential equations (PDEs) into non-dimensional ordinary differential equations (ODEs). Method: The system of governing ordinary differential equations (ODEs) with boundary conditions (BCs) are highly non-linear in nature. To handle these non-linear ODEs, we use a numerical technique called BVP Midrich scheme which uses the midpoint method to acquire the numerical solution of the governing problem. The solutions of the governing problem are obtained by utilizing Maple software. Results: Effect of different involved controlling parameters on the velocity profiles, temperature and concentration distributions are analyzed graphically. Additionally, the numerical data for local Nusselt and Sherwood numbers are also tabulated. The reduction in heat transfer rate at the wall is noticed against thermoporesis and Brownian motion parameters, respectively. The concentration gradient at the wall reduces with an increment in mass transfer parameter.